2020
DOI: 10.3389/fonc.2020.00134
|View full text |Cite
|
Sign up to set email alerts
|

The Rare Variant rs35356162 in UHRF1BP1 Increases Bladder Cancer Risk in Han Chinese Population

Abstract: Background: Seventeen loci have been found to be associated with bladder cancer risk by genome-wide association studies (GWAS) in European population. However, little is known about contribution of low-frequency and rare variants to bladder cancer susceptibility, especially in Eastern population. Methods:We performed a three-stage case-control study including 3,399 bladder cancer patients and 4,647 controls to identify low-frequency and rare variants associated with bladder cancer risk in Han Chinese. We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Moreover, miR-143 restrained the expression of FAM83F and thereby refrained the proliferation, migration, and invasion and induced G1/G0 phase arrest of ESCC cells ( Mao et al, 2016 ). Besides, FAM83F was also found high expression in papillary thyroid cancer ( Fuziwara et al, 2019 ). Furthermore, the functional study had shown that MiR-650 expression in glioma tissues was greatly decreased, while the expression of FAM83F was remarkably up-regulated and MiR-650 could promote cell proliferation through facilitating the expression of FAM83F ( Xu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, miR-143 restrained the expression of FAM83F and thereby refrained the proliferation, migration, and invasion and induced G1/G0 phase arrest of ESCC cells ( Mao et al, 2016 ). Besides, FAM83F was also found high expression in papillary thyroid cancer ( Fuziwara et al, 2019 ). Furthermore, the functional study had shown that MiR-650 expression in glioma tissues was greatly decreased, while the expression of FAM83F was remarkably up-regulated and MiR-650 could promote cell proliferation through facilitating the expression of FAM83F ( Xu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, studies have demonstrated abnormal expression in some members of the FAM83 family and their prognostic value. For example, Fuziwara et al (2019) reported that FAM83F , a novel oncogenic protein, was overexpressed in thyroid cancer and cross-regulated MAPK and TGF signaling pathways to promote the biological behavior and differentiation of thyroid follicular cells. FAM83B was recently identified as a novel oncogene involved in activating CRAF/MAPK signaling and driving epithelial cell transformation ( Cipriano et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to β-catenin accumulation in the cytosol, increased nuclear translocation of activated β-catenin, interactions with members of the T-cell factor (TCF4) transcription factor family, and stimulation of β-catenin-dependent gene expression leading to increased cell proliferation and growth ( 196 ). The role of Wnt/β-catenin signaling in the development of colorectal cancer is now well-recognised ( 197 ) and a functional interaction between estrogen signaling and Wnt/β-catenin pathways has been reported in human colon cancer cells ( 198 ). Recent studies have shown convergence between KCNQ1 and β-catenin regulatory pathways in CRC and the molecular mechanisms regulating KCNQ1:β-catenin interactions and their effects on CRC cell differentiation, proliferation, and invasion ( 199 ).…”
Section: Sexual Dimorphism Of Ion Channel Function In Crcmentioning
confidence: 99%
“…Emerging evidence has revealed that low-frequency variants are associated with prostate [20], lung [18], ovarian [21], and breast cancers [22], but the role of low-frequency variants in the bladder cancer risk remains unclear. Although our previous study described an exome chip analysis and showed that the rare variant rs35356162 in UHRF1BP1 increases the bladder cancer risk [23], the sequencing depth and economic efficiency are inferior to targeted next-generation region sequencing. In addition, targeted sequencing of known risk-associated regions to identify the effects of low-frequency or rare variants on disease has been recognized as a useful approach to help elucidate a further proportion of disease heritability [16,24,25].…”
Section: Introductionmentioning
confidence: 99%